In situ effect of an erosive challenge on different restorative materials and on enamel adjacent to these materials - Rios, Daniela; Honorio, Heitor Marques; Francisconi, Luciana Favaro; Magalhaes, Ana Carolina [UNESP]; de Andrade Moreira Machado, Maria Aparecida; Rabelo Buzalaf, Marilia Afonso (Elsevier B.V., 2008)
Objectives: This in situ study evaluated the effect of an erosive challenge on different restorative materials and on enamel restored with these materials, as well as the ability of these materials to protect the adjacent enamel against erosion.Methods: Ten volunteers wore palatal devices with eight bovine enamel blocks, randomly selected and distributed into two vertical rows, corresponding to the following groups: GI/GV, resin-modified glass ionomer; GII/GVI, conventional glass ionomer; GIII/GVII, composite resin; GIV/GVIII, amalgam. one row (corresponding to groups I-IV) was immersed in a cola drink and the other row (corresponding to groups V-VIII) was subjected to saliva only. The palatal device was continuously worn for 7 days and only half of the appliance (groups I-IV) was immersed in the soft drink (Coca-Cola (R), 150 mL) for 5 min, three times a day. The study variables comprised the wear (profilometry, mu m) and the percentage of surface microhardness change (%SMHC). Data were tested for significant differences by two-way ANOVA and Tukey's tests (p < 0.05).Results: Considering the restorative materials, for %SMHC and wear, there were no differences among the materials and between the saliva and the erosive challenge. For enamel analyses, the erosive challenge promoted a higher wear and %SMHC of the enamel than did the saliva. There were no significant differences in wear and %SMHC of the enamel adjacent to the different restorative materials.Conclusion: This research data suggest that there is little %SMHC and wear of the studied restorative materials and none of them had a preventive effect against erosion on adjacent enamel, which showed a pronounced wear. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: dental erosion; enamel; dental materials; in situ